Effects of Urban Growth on Settlement Pattern of Tripoli Libya - Mohamed Farag, Dr. Iman; Shaban Algeblawi, Mr. Hamed (Aljameai)
ABSTRACT: Human settlements are essential, apparently fixed yet changing, landscape ecology characteristics that have sparked a number of research owing to their importance in human existence. The consequences of urban expansion settlement pattern in Tripoli were investigated in this article, with a focus on the role of economic, social, and political elements in urbanization. Regardless of the actuality that municipal planning authorities created as well as developed a number of projects and planning generation series, there have been issues and challenges in dealing with Libya’s rapid urbanization, that has ultimately resulted in urbanization process and a shortfall of housing services. This has resulted in a tremendous and haphazard urbanization, resulting in the loss of vast agricultural or green landscapes in favor of new metropolitan settlements. It suggests that there have been persistent problems in regulating and limiting urban development inside urban centres in general, and Tripoli in particular, based on archival evidence, interviews, and intimate knowledge of the research region. In this study, I looked at the importance of each aspect of urban expansion and urbanization in the Libyan example VS Africa as a whole, using theories of Myers. المستخلص: تعد المستوطنات البشرية من الخصائص الأساسية لبيئة المناظر الطبيعية ، والتي يبدو أنها ثابتة ومتغيرة على ما يبدو ، والتي أثارت عددًا من الأبحاث نظرًا لأهميتها في الوجود البشري. تم التحقيق في عواقب نمط التوسع العمراني الاستيطاني في طرابلس في هذا المقال ، مع التركيز على دور العناصر الاقتصادية والاجتماعية والسياسية في التحضر. بغض النظر عن الواقع الذي أنشأته سلطات التخطيط البلدي وكذلك طورت عددًا من المشاريع وسلسلة التخطيط التوليدية ، كانت هناك قضايا وتحديات في التعامل مع التحضر السريع في ليبيا ، مما أدى في النهاية إلى عملية التحضر ونقص في خدمات الإسكان. وقد أدى ذلك إلى تحضر هائل وعشوائي ، مما أدى إلى فقدان مساحات شاسعة من الأراضي الزراعية أو الخضراء لصالح مستوطنات حضرية جديدة. ويشير إلى وجود مشاكل مستمرة في تنظيم والحد من التنمية الحضرية داخل المراكز الحضرية بشكل عام ، وطرابلس على وجه الخصوص ، بناءً على الأدلة الأرشيفية ، والمقابلات ، والمعرفة الوثيقة بمنطقة البحث. في هذه الدراسة ، نظرت إلى أهمية كل جانب من جوانب التوسع الحضري والتحضر في المثال الليبي ضد إفريقيا ككل ، باستخدام نظريات مايرز.